KOMUNIKASI INTERPERSONAL MANAJEMEN, PELATIH, DAN ATLET SEPAK BOLA KOTA BANDAR LAMPUNG DALAM MENINGKATKAN MOTIVASI BERPRESTASI - Muhammad Fajril Rifaldo; Riyan Jaya Sumantri; Alifia Ramadhina Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the importance of interpersonal communication between management, coaches, and football athletes in Bandar Lampung City in enhancing achievement motivation in football. Using a qualitative narrative approach, the study aims to understand how five key attitudes openness, empathy, supportiveness, positivity, and equality contribute to communication effectiveness and their impact on team performance. Through purposive sampling, data were collected using semi-structured interviews, observations, and documentation, which were then analyzed to identify communication patterns influencing athletes’ motivation and performance.The results indicate that openness in communication helps create an environment characterized by mutual respect and honesty, while empathy strengthens emotional relationships within the team. Support provided by management and coaches significantly assists athletes in overcoming challenges, while positivity and equality establish a foundation for productive and harmonious communication. Through effective interpersonal communication, management, coaches, and athletes are able to build a cohesive team, maintain focus on shared goals, and maximize their potential to achieve optimal performance. These findings underscore the importance of interpersonal communication in sports development, particularly in enhancing motivation and team achievement in football in Bandar Lampung City.